Evaluation of an Online Judge for Concurrent Programming Learning - Hidalgo-Cespedes, Jeisson (Proceedings of the Latin American Computing Conference (Online), 2023)
Online judges are tools that can significantly help the learning of programming. However, previous studies have found that existing tools provide little level of satisfaction of the teachers' and students' needs. One of these requirements is the learning of concurrent and distributed programming, despite the increasing importance of these computing paradigms. This article reports the implementation of an online judge prototype for concurrent programming and its evaluation through a quasi-experiment. Although no significant differences were found with respect to the traditional tools used in the course, indications were obtained that the students who used the online judge prototype produced solutions with fewer programming anomalies. Regarding motivational aspects, students reported a better user experience, especially those who were able to contrast the online judge against the traditional development tools used in the course.